Inflammatory Markers in Hyperlipidemia: From Experimental Models to Clinical Practice - Siasos, Gerasimos; Tousoulis, Dimitris; Oikonomou, Evangelos; Zaromitidou, Marina; Stefanadis, Christodoulos; G. Papavassiliou, Athanasios (Current Pharmaceutical Design, 2011)
The role of inflammation in the development and progression of cardiovascular diseases is well established. Systemic inflammation and immune system play a central role in atherogenesis. The strong dependence of the atherosclerotic process on both a state of continuous low grade inflammation and the presence of lipid abnormalities gave impetus to research the association between hyperlipidemia and inflammatory status. In experimental and clinical studies, several inflammatory markers such as C-reactive protein, tumor necrosis factor-alpha, interleukin 6, nuclear factor kappa-β, adhesion molecules, serum amyloid-α, lipoprotein-associated phospholipase A2, fibrinogen and sCD40 ligand are associated with lipids level. Although, cholesterol lowering treatment has several important beneficial effects, there is still little clinical experience or data from clinical trials, in order to treat patients with hyperlipidemia and impaired inflammatory status.
Keywords: TNF-α